(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2016)
The combination of quantitative and qualitative methodologies is frequently used for researching on Second Language Studies (SLA). In this paper, evolution and usage of some instruments in researching motivation and attitudes in SLA are reviewed. Also, some reflections on future research trends of these variables in the field of the Spanish as a Foreign Language are exposed from a wider and dynamic approach.